Harp seal body condition and trophic interactions with prey in Norwegian high Arctic waters in early autumn. (February 2021) - Haug, Tore; Biuw, Martin; Gjøsæter, Harald; Knutsen, Tor; Lindstrøm, Ulf; MacKenzie, Kirsteen M.; Meier, Sonnich; Nilssen, Kjell T.
Highlights: Even though small sample sizes and differences in age compositions made it challenging to compare the Barents Sea harp seal body condition between sampling periods, there were some indications of a possible decline over the past 25 years. Current short-term (analyses of digestive tract contents) prey use by the seals revealed that pelagic amphipods ( Themisto libellula) and polar cod ( Boreogadus saida ) were the most prominent prey species, as also observed for harp seals on their northern feeding grounds in the Barents Sea during autumn nearly 3 decades ago. The long-term diet of the seals, based on stable isotope and fatty acid composition, was reflected well in the short-term stomach contents composition. Results from acoustic and trawl surveys conducted concurrently with the seal sampling confirmed that the pelagic amphipods were by far the most abundant prey observed on the assumed harp seal feeding grounds, followed by krill ( Thysanoessa sp.), Atlantic cod ( Gadus morhua ) and polar cod. Prey-preference analyses revealed that the seals displayed a clear positive preference for polar cod and random feeding and negative preference for amphipods and krill, respectively, i.e. amphipods and krill were consumed in less proportions than observed in the environment. Abstract: In September 2016, a marine ecosystem survey covered all trophic levels from phytoplankton to seals in the Arctic Ocean to the west and north of Svalbard. At the ice edge, 26 harp seals were sampled to assess whether recent environmental changes had affected their diets and body condition by comparing our current results with previous investigations conducted 2–3 decades ago in the northern Barents Sea, when the ice edge was located much further south. Our results suggest that the body condition was slightly but significantly lower for one year and older seals in 2016 compared with seals sampled in the early 1990s. Furthermore, we confirmed previous findings that polar cod ( Boreogadus saida) and the pelagic hyperiid amphipod Themisto libellula still dominate the seal diet. One consequence of current ice edge localisation north of Svalbard is that the water depth underneath is now 500 m and deeper, which probably explains the absence of bottom associated species, and the presence of species such as Atlantic cod ( Gadus morhua) and blue whiting (Micromesistius poutassou) as alternative species in addition to polar cod and T. libellula in the seal diets. Stable isotope data also suggest possible long-term importance in the seal diet of T. libellula and of low trophic level benthopelagic prey such as the squid Gonatus fabricii over mid-trophic level pelagic fishes, but with a strong component of small, benthopelagic fish such as blue whiting. The long-term importance of pelagic crustaceans was also suggested from the fatty acid analyses. Assessment of the abundance of prey showed that T. libellula was by far the most abundant prey species in the upper water layers, followed by krill (mainly Thysanoessa inermis ), Atlantic cod and polar cod. Prey-preference analyses indicated that polar cod was the most preferred prey species for the seals.